More of the Same, Only Worse: COVID-19 and the Administrative Burdens Facing Loved Ones of Incarcerated Men - McDonald, Alysha Danielle (The British journal of criminology, 2023)
Over the course of the COVID-19 pandemic, officials have introduced measures to preserve the health of incarcerated individuals and prison employees. To understand the impact of COVID-related correctional policies on individuals with incarcerated friends and family members, we conducted 181 longitudinal interviews from April 2020 to January 2021 with 29 such ‘loved ones.’ Participants emphasized concerns about (1) health and safety; (2) unclear, unpredictable and untrusted communications; and (3) diminished personal intimacy. We analyze these findings using an ‘administrative burden’ framework and discuss possible reforms. We also suggest a wider applicably of this framework for studying individuals who have diverse encounters with the criminal justice system.